2011
DOI: 10.1371/journal.pgen.1001378
|View full text |Cite
|
Sign up to set email alerts
|

GWAS of Follicular Lymphoma Reveals Allelic Heterogeneity at 6p21.32 and Suggests Shared Genetic Susceptibility with Diffuse Large B-cell Lymphoma

Abstract: Non-Hodgkin lymphoma (NHL) represents a diverse group of hematological malignancies, of which follicular lymphoma (FL) is a prevalent subtype. A previous genome-wide association study has established a marker, rs10484561 in the human leukocyte antigen (HLA) class II region on 6p21.32 associated with increased FL risk. Here, in a three-stage genome-wide association study, starting with a genome-wide scan of 379 FL cases and 791 controls followed by validation in 1,049 cases and 5,790 controls, we identified a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 31 publications
12
97
0
Order By: Relevance
“…The variant rs2647012, a marker for DRB3/DRB5 lineages [53] and a protective marker for lymphoma [34], showed a statistically significant risk association among Hispanics, but not in non-Hispanics (P interaction = 0.003 for ethnicity). Our study appears to be the first looking at a…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The variant rs2647012, a marker for DRB3/DRB5 lineages [53] and a protective marker for lymphoma [34], showed a statistically significant risk association among Hispanics, but not in non-Hispanics (P interaction = 0.003 for ethnicity). Our study appears to be the first looking at a…”
Section: Discussionmentioning
confidence: 95%
“…We re-examined five previously discovered single nucleotide polymorphisms (SNPs) of known associations to leukemia (rs7089424, rs10821936, rs10994982, rs4132601, and rs2239633), along with three HLA region susceptibility markers for lymphomas, since lymphoma and ALL both stem from lymphoid cells. These included rs2395185, a marker of HLA DRB4 lineage [23] which has previously shown associations with major leukemias including childhood ALL [24,25] and other diseases including Hodgkin lymphoma [26], lung cancer [27], rheumatoid arthritis [28], asthma [29], and ulcerative colitis [30][31][32]; rs10484561, which has been shown to be a strong risk marker in follicular lymphoma (FL) [33]; and rs2647012, which is a protective marker for FL [34]. These SNPs were examined in a multiethnic sample (non-Hispanic Whites, Hispanic Whites, and Blacks) from Houston, Texas to assess their association with ALL.…”
Section: Introductionmentioning
confidence: 99%
“…Additional evidence of the integral role of the immune system in lymphomagenesis can be seen from epidemiologic studies that examined polymorphisms in genes coding for cytokines that modulate the inflammatory process or are linked to B cell activation (Wang et al 2007;Ambinder et al 2010;Skibola et al 2010). In addition, recent genomewide association studies (GWAS) of the follicular subtype of NHL identified association with two variants within the human leukocyte antigen (HLA) region (Skibola et al 2009;Smedby et al 2011).…”
Section: Lymphomagenesis: the Role Of The Immune Systemmentioning
confidence: 99%
“…However, a potential role of obesity in lymphomagenesis cannot be excluded because, on one hand, several studies showed that obesity is a lowgrade chronic inflammatory state and, on the other hand, a chronic inflammatory condition has been linked to NHL risk in previous epidemiological studies (Smedby et al 2011). It therefore seems that a broader investigation of markers of the immune system, such as, for instance, markers of chronic B cell activation (sCD30), might be warranted to further investigate the possible immune mediated association between obesity and NHL.…”
Section: Obesitymentioning
confidence: 99%
“…These included rs2395185, a marker of HLA DRB4 lineage [38] which has previously shown risk associations with major leukemias including childhood ALL and other diseases [39][40][41][42][43][44][45][46][47][48][49]; rs10484561, which has been shown to be a strong risk marker in follicular lymphoma (FL) [50]; and rs2647012, which is a protective marker for FL [51]. These SNPs were examined in a multi-ethnic sample (non-Hispanic Whites, Hispanic Whites, and Blacks)…”
Section: Introductionmentioning
confidence: 99%